The correlation of D‐dimer to stroke diagnosis within 24 hours: A meta‐analysis. Issue 3 (4th February 2022) - Ahmad, Adeel; Islam, Zara; Manzoor Ahmad, Saad; Sarfraz, Zouina; Sarfraz, Azza; Felix, Miguel; Cherrez‐Ojeda, Ivan
Abstract: Background: Diagnosing D‐Dimer early is essential to optimize clinical treatment and quality of life and reduce mortality. This study aims to identify the difference of D‐Dimer levels (ng/ml) in patients with stroke within the 6‐ and 24‐h period compared to patients that mimic stroke. Methods: An electronic database search across PubMed/MEDLINE, Cochrane, Web of Science, CINAHL, EMBASE, and Scopus was conducted until December 10, 2021. Studies were eligible if they included adult patients with stroke compared to stroke mimics or controls reporting D‐Dimer values. Quality assessment was conducted using GRADE. The standardized mean difference and 95% confidence intervals were calculated in addition to the difference of means in the crude form. Heterogeneity was assessed using Cochran's Q statistic and the I 2 index. A random‐effects model was used. The statistical analysis was conducted using RevMan 5.4. Results: Out of 2901, there were 318 (11%) participants from upper‐middle‐income countries, whereas the others were from high‐income countries. Large positive effect size was found for D‐Dimer in the stroke group (Cohen's d  = 2.82 [1.73–3.9]; p  < 0.00001), meaning that those with stroke had higher D‐Dimer values on presentation compared to the stroke mimics/controls. A large difference in means was found in the two groups (MD = 685.1 [324.2, 1045.99]; p  < 0.00001), suggesting that there was a significantly higher laboratory value in the stroke group. Conclusion: Our findings must be used in caution as the most reliable diagnostic tests for stroke are CT and MRI. Laboratory testing such as D‐Dimer values is a valuable clinical adjuvant in diagnosing total stroke. Abstract : This meta‐analysis finds that large positive effect size was found for D‐Dimer in the stroke group ( d  = 2.82) on presentation compared to the stroke mimics/controls.